Berketuhanan dalam Perspektif Kepercayaan Sunda Wiwitan - Indrawardana, Ira (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2014)
By referring to the variety of cultures that have emerged and flourished in Indonesia, the author wants to figure the depth of ‘belief’ in God in relation to the respective cultural and spiritual expressions and through the rituals performed by the people of this belief (kepercayaan). Because of the influence of ‘Western’ beliefs brought into Indonesia by the colonialists in the past, the life of the people believing in God from within their own local beliefs together with the diversity of their cultures and spiritualities seem to have been marginalised. What is needed is a sort of new paradigm to view and value the local beliefs in the face of the so-called ‘official religions’ in Indonesia. This greater appreciation to the people of the local beliefs is in the line with the growing awareness of plurality of societies in this land. Efforts to recognise and understand the essence and values in the system of the local belief are of great importance. The author tries to explore how the doctrines of the belief Sunda Wiwitan develop by starting to browse the historical aspect of Manusia Sunda (‘Sundanese human being’) within its religious context and the other related elements in this system of belief. What is most important for the adherents of Sunda Wiwitan is not so much the frequence of praying to or worshiping God as the effort of every individual to maintain the attitude and deeds as a human being that keep the harmony of relation with the other human beings, the surrounding nature with all its contents, and God.